Ethnobotany of Food Plants Based on Land Characteristics in Lombok Island - Ihwan, Khaerul Ihwan; Atika, Baiq Naili Dewi; Nitami, Dian (Jurnal Biologi Tropis, 2024)
The ethnobotanical study of food crops is very important to be carried out because it can be a means of natural resource conservation, social and economic sustainability of local communities. The diversity of food crops on the island of Lombok reflects the interaction between humans and the environment as well as the cultural values contained in the practice of using food crops in daily life. The objectives of this study are to: a) identify food crops on the island of Lombok based on land characteristics, b) find out the distribution of food crops on the island of Lombok based on land characteristics, and c) find out how food crops are used by the community on the island of Lombok.  The sample was determined using the purposive sampling technique. Data were collected through semi-structured interviews and then plant specimens were collected accompanied by key informants in the field. Data analysis was carried out in a qualitative descriptive manner after being processed in Microsoft Excel using simple statistical techniques. Based on the results of the study, about 64 species of food crops were found. Land characteristics consist of wetlands, sandy lands, and dry lands. A total of 46 species of food crops were found in rice fields with wetland/clay characteristics. A total of 30 species of food crops were found on land with sandy characteristics and as many as 18 species of food crops were found on hilly land with dry land characteristics. The use of food crops by the community is ground as much as 10%, mashed as much as 12%, cooked as much as 60% and eaten raw as much as 40%. Based on the results of this study, it can be concluded that food crops are more commonly found on land with wetland or rice field characteristics and the use of food crops is most obtained by cooking.